Entrepreneurial Motivation and Increased Creativity STIKES Bhakti Husada Bengkulu students - Wiwin Saputra; Ahmad Saleh; Karona Cahya Susena (UKInstitute, 2023)
Entrepreneurial motivation is an internal drive to grow and develop new businesses by accessing information about entrepreneurial opportunities. In addition to motivation, entrepreneurial creativity is also needed as the ability to generate new ideas and product innovation in capturing opportunities. So that someone who has entrepreneurial motivation and creativity is expected to be ready to enter the world of entrepreneurship to win the competition. This community service activity aims to provide socialization about entrepreneurship, as well as generate motivation and increase entrepreneurial creativity for Semester VII students of Stikes Bhakti Husada Bengkulu. The method used is group counseling method. Group counseling or group approach is an extension related to the goals of group counseling. The results of this activity indicate that most of the targets have understood entrepreneurship and have motivation and creativity as things that cannot be ignored in entrepreneurship. This community service activity is able to contribute to increasing community empowerment in the field of motivation and creativity to prepare an entrepreneurial mentality. So that in the end the students of Stikes Bhakti Husada Bengkulu can be moved to start a business more seriously and increase their income, both those who are still active students and later become alumni.